2016
DOI: 10.1001/jamapsychiatry.2016.0637
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Cannabis Use and Physical Health Problems in Early Midlife

Abstract: Importance Following major policy changes in the United States, policy makers, clinicians, and the general public seek information about whether recreational cannabis use is associated with physical health problems later in life. Objective To test associations between cannabis use over twenty years and a variety of physical health indices at early midlife. Design A 38-year, prospective, longitudinal study of a representative birth cohort. Setting The Dunedin Multidisciplinary Health and Development Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 55 publications
0
86
0
2
Order By: Relevance
“…Other studies showed persistent marijuana use was associated with long-lasting cognitive impairment, and that cessation of marijuana use does not fully restore neuropsychological functioning, especially among those marijuana users of adolescent-onset (Meier et al, 2012, Riba et al, 2015). Another study found that marijuana use for up to 20 years was associated with periodontal disease but not with other physical health measures in early midlife (Meier et al, 2016). In this study, we did not detect any appreciable difference in reporting suboptimal SRH among regular marijuana smokers with and without current tobacco stratified by status of their past 30- or 60-day regular marijuana smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed persistent marijuana use was associated with long-lasting cognitive impairment, and that cessation of marijuana use does not fully restore neuropsychological functioning, especially among those marijuana users of adolescent-onset (Meier et al, 2012, Riba et al, 2015). Another study found that marijuana use for up to 20 years was associated with periodontal disease but not with other physical health measures in early midlife (Meier et al, 2016). In this study, we did not detect any appreciable difference in reporting suboptimal SRH among regular marijuana smokers with and without current tobacco stratified by status of their past 30- or 60-day regular marijuana smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The data on marijuana use and cardiac disease have not shown compelling evidence for concern. One recent 20-year comparison of daily tobacco versus marijuana smokers showed only increased risk for periodontal disease with cannabis, whereas tobacco users had expected increases in lung, cardiac, and metabolic (wait circumference, lipid profile, HgA1C, body weight) 17 risk factors. Cannabis appears to have some anti-inflammatory properties; according to the National Academies report, there is insufficient evidence to support any conclusions about the impacts of cannabis on other immune functions.…”
Section: Safetymentioning
confidence: 99%
“…Marijuana users have greater oral cavity deterioration than non-users, with increased risk of caries and periodontal disease. 2,3 Higher levels of decayed, missing and filled teeth (DMFT) and bacterial plaque indices have been found in marijuana users than in non-users. 1,4 Moreover, users are more prone to oral infections, possibly due to alterations in oral immunology, 2 and drug use can be associated with dysplastic changes and potentially malignant disorders of the oral mucosa, increasing the incidence of squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…4 Dentists can evaluate oral alterations that might be related to drug use, such as enamel erosion caused by contact with cocaine/crack, the presence of generalized inflammation of the oral mucosa caused by marijuana, as well as dry mouth, gingival/periodontal disease and tooth decay as a result of poor oral hygiene. 3,4,8,12 The relationship between illicit drug use and oral tissues response is lacking in the literature. Therefore, the aim of this study was to compare the oral health status of users of illicit drugs, such as marijuana and cocaine/crack, with that of non-users.…”
Section: Introductionmentioning
confidence: 99%